Clock gene period in the Chagas disease vector Triatoma infestans (Hemiptera: Reduviidae) - Stroppa, María Mercedes; Giménez, Ignacio; García, Beatriz A. (American Society of Tropical Medicine and Hygiene, 2023)
7 p.